Analisis faktor-faktor yang mempengaruhi profitabilitas dengan manajemen laba sebagai variabel moderasi - Marlinaayu Dhiyana Kriswidyaningrum; Sri Hermuningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
This study was conducted to examine the effect of Company Size, Debt to Equity Ratio, Total Asset Turnover to Profitability with Profit Growth as Variabel Moderation Available in Consumer Bargaining Industries in 2014-2018). The population in this study is the consumer goods industry which is listed on the Indonesia Stock Exchange (IDX). Sampling was done using a purposive sampling method. This study contains 11 companies that met the criteria. Data analysis uses multiple regression methods and Moderated Regression Analysis (MRA). Based on research that has been done shows that Company Size, Debt to Equity Ratio, Total Assets Turn Over and affect profitability. While profit growth can moderate Company Size, Debt to Equity Ratio, Total Assets Turn Over Total Assets to profitability.Keywords: Company Size, Debt to Equity Ratio, Total Asset Turnover, Profit Growth, Profitability